Dose-optimized microbial inoculants reshape grape rhizosphere microbiota and enhance fruit quality - Chang, Xiaojian; Chen, Ji; Zhao, Kegang; Wang, Tao; Yang, Yong; Jia, Xinyue; Hu, Bingbing; Yu, Yanmei; Li, Fangxiang; He, Yanhui; Wu, Zhansheng (Frontiers in Microbiology, 2025)
IntroductionSoil serves as a critical habitat for plant growth, harboring diverse microbial communities that profoundly influence soil quality, plant health, and fruit quality. This work aimed to evaluate the potential of microbial inoculants application at varying doses on improving soil health, enhance plant stress resistance, and promote fruit quality.MethodsRhizosphere microbial communities across five treatment groups—CK (no inoculant), T1 (45 L/ha), T2 (90 L/ha), T3 (135 L/ha), and T4 (180 L/ha)—were analyzed using high-throughput sequencing on the Illumina NextSeq platform. Concurrently, soil physicochemical properties from the rhizosphere, alongside physiological and biochemical parameters of grape leaves and fruit quality indicators, were measured for all treatments.ResultsThe results indicated that inoculant application significantly increased the relative abundance of bacterial phyla Proteobacteria and Actinobacteria, along with the genera Bacillus, Nitrospira, and Pseudomonas. Concurrently, a decrease in the relative abundance of fungi from the phylum Ascomycota (e.g., Penicillium, Fusarium) was observed, whereas an increase was noted for phyla Mortierellomycota and Basidiomycota, and genera such as Mortierella and Solicoccozyma. Furthermore, microbial inoculant applications (T1–T4) led to significant changes in soil parameters (e.g., nutrient availability and enzyme activity), plant physiological indicators (e.g., antioxidant enzyme activity), and fruit quality metrics (e.g., soluble sugars and vitamin C content). The most pronounced changes were observed under the T2 treatment (90 L/ha), whereas higher doses (T3–T4) resulted in diminished responses together with increased costs, indicating a clear dose-dependent effect.ConclusionIn summary, the application of compound microbial inoculants, particularly at optimized doses, was associated with shifts in rhizosphere microbial community structure and improvements in soil–plant system metrics, suggesting the potential to contribute to sustainable agricultural management.